2015
DOI: 10.4161/2162402x.2014.992749
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivoexpanded human circulating Vδ1 γδT cells exhibit favorable therapeutic potential for colon cancer

Abstract: Gamma delta T (γδT) cells are innate-like lymphocytes with strong, MHC-unrestricted cytotoxicity against cancer cells and show a promising prospect in adoptive cellular immunotherapy for various malignancies. However, the clinical outcome of commonly used Vγ9Vδ2 γδT (Vδ2 T) cells in adoptive immunotherapy for most solid tumors is limited. Here, we demonstrate that freshly isolated Vδ1 γδT (Vδ1 T) cells from human peripheral blood (PB) exhibit more potent cytotoxicity against adherent and sphere-forming human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 42 publications
5
87
0
Order By: Relevance
“…One report showed positive responses and persistence in spleen and bone marrow upon ACT in mice up to 39 days after transfer (30), although it is not clear whether the recovered cells retained effector phenotype and if there was a wide distribution to other organs. Another report provided in vivo efficacy data in human colon carcinoma xenografted mice (34). Of note, this interesting study confirmed the greater antitumor efficacy of Vd1 þ cells over Vd2 þ gd T cells, which correlated with their expression of NCRs, suggesting that colon carcinoma could be an interesting target for DOT cells.…”
Section: Discussionsupporting
confidence: 49%
“…One report showed positive responses and persistence in spleen and bone marrow upon ACT in mice up to 39 days after transfer (30), although it is not clear whether the recovered cells retained effector phenotype and if there was a wide distribution to other organs. Another report provided in vivo efficacy data in human colon carcinoma xenografted mice (34). Of note, this interesting study confirmed the greater antitumor efficacy of Vd1 þ cells over Vd2 þ gd T cells, which correlated with their expression of NCRs, suggesting that colon carcinoma could be an interesting target for DOT cells.…”
Section: Discussionsupporting
confidence: 49%
“…No significant differences of the proportion of Vd1 T cells were found among the AR and HC groups. Although the liver is one of the organs that Vd1 T cells localize primarily in [24], we observed rare Vd1 T cells in control livers, corresponding with the distribution of murine Vd1 T cells [25]. Correlation analysis showed no correlation between Vd1 T cells and levels of serum ALT, AST, ALP, GGT, TBil and TBA of PBC.…”
Section: Discussionmentioning
confidence: 54%
“…The present study indicates that γδ T cells derived from the pleural effusion could be a source of adoptive γδ T cell immunotherapy in lung cancer. Unlike for Vδ2 T cells, which respond to phosphoantigens, there is no protocol concerning the expansion of Vδ1 + populations ex vivo, although a recent study indicated that PHA and IL-7 may be candidates to facilitate expansion of the Vδ1 subtype in circulating γδ T cells (13). However, the present authors have been unable to obtain a satisfactory result on the ex vivo expansion of Vδ1 or Vδ2 cells, either using PHA and IL-7 stimulation or zoledronic acid when using the γδ T cells isolated from pleural effusion in advanced NSCLC (Bao et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Vδ2 cells, Vδ1 cells do not respond to phosphoantigens, but are able to recognize the MHC class I chain-related molecules A and B (12). A recent study suggested that Vδ1 + T cells derived from the PB of normal donors are able to undergo ex vivo expansion by administration of phytohemagglutinin (PHA) and interleukin-7 (IL-7) (13); moreover, Vδ1 T cells exhibit more favorable antitumor activity than Vδ2 T cells in colon cancer (13). Ex vivo-expanded circulating γδ T cells represent a promising prospect in antitumor activities and are a potential candidate treatment for various malignancies, including non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%